Effects of 12 Weeks of Atorvastatin Therapy on Myocardial Fibrosis and Circulating Fibrosis Biomarkers in Statin-NaïVe Patients with Hypertension with Atherosclerosis. Issue 7 (October 2016) - Chang, Yi-Yao; Wu, Yen-Wen; Lee, Jen-Kuang; Lin, Yu-Min; Lin, Yen-Ting; Kao, Hsian-Li; Hung, Chi-Sheng; Lin, Hung-Ju; Lin, Yen-Hung
The purpose of this study was to assess the effects of 12 weeks of atorvastatin treatment on myocardial fibrosis in patients with hypertension with atherosclerosis. 15 statin-naïve participants (11 males; mean age 67±10 years) with atherosclerosis were given atorvastatin (40 mg/day) for 12 weeks and underwent echocardiography including ultrasonic tissue characterization by cyclic variation of integrated backscatter (CVIBS). Serum galectin-3 and fibrosis markers including aminoterminal propeptide of type III procollagen (PIIINP), matrix metalloproteinase-2, metalloproteinase-9, and tissue inhibitor of metalloproteinase-1 (TIMP-1) were also analyzed. After 12 weeks of atorvastatin (40 mg/day) treatment, serum total cholesterol and low-density lipoprotein cholesterol decreased significantly (204±31 to 140±24 mg/dL and 133±26 to 69±17 ng/mL, respectively, both p<0.001). In myocardial fibrosis analysis, CVIBS increased significantly (6.6±1.9 to 8.5±2.7 dB, p=0.024). In addition, the circulating fibrosis markers serum PIIINP and TIMP-1 decreased significantly (9.5±2.7 to 6.4±1.4 ng/mL, p=0.012 and 299±65 to 250±45 ng/mL, p=0.024, respectively). 12 weeks of medium dose atorvastatin treatment resulted in a significant reduction in myocardial fibrosis as evaluated by morphofunctional parameters and plasma markers of tissue fibrosis. Trial registration number: NTC00172419; results.